Mobile Application for Zakat, Infaq and Sadaqah (ZIS) Management Based on Artificial Intelligence (AI) Chatbot - Rama Putra, Gustian; Ismangil, Agus; Fahdin, Moch.; Arsal, Muhammad (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2025)
As public awareness continues to grow regarding the importance of zakat, infaq and sadaqah (ZIS) as tools for social and economic welfare in Indonesia, there is an increasing need for innovation in how these charitable contributions are managed. One promising solution is the development of a mobile application that uses chatbot technology to make the process of giving and managing ZIS more efficient, transparent and user friendly. This study focuses on designing and building such a mobile app, using the waterfall model for software development. The process includes defining requirements, designing the system, analyzing the features, implementing the chatbot, and testing the application. The app is built to provide an interactive experience that helps users easily perform ZIS-related transactions, while also offering personalized information based on their needs. Testing results show that the app successfully supports essential functions like user registration, zakat payment, and access to ZIS information. It was also tested for compatibility and UI stability begin with Android 10 (Q) and above. While earlier versions such as Android 8 and 9 pose risks related to SDK support and performance, versions Android 12 to 14 demonstrate optimal performance and system stability. Android 15, still in beta, shows positive early results but requires further testing due to its ongoing development and potential SDK changes on multiple devices to ensure performance across different platforms. The findings indicate that the app runs smoothly, is easy to use, and is accessible to the broader community. Overall, this research presents a meaningful contribution to the modernization of ZIS management in Indonesia by leveraging digital technology to better serve the public.